Biofeedback Low Vision Rehabilitation with Retimax Vision Trainer in Patients with Advanced Age-related Macular Degeneration: A Pilot Study. (2nd April 2020) - Verdina, Tommaso; Piaggi, Stefania; Peschiera, Riccardo; Russolillo, Valeria; Ferraro, Vanessa; Chester, Johanna; Mastropasqua, Rodolfo; Cavallini, Gian Maria
ABSTRACT: Purpose: To evaluate the effectiveness of Visual Evoked Potential (VEP) biofeedback rehabilitation in selected low vision patients with advanced age-related macular degeneration (AMD). Design: Retrospective observational cohort study. Methods: Patients affected by advanced AMD, central macular atrophy with unstable fixation and best corrected visual acuity (BCVA) between 20/100 and 20/320 were considered. Selected patients underwent fundus photography and microperimetry with fixation analysis for the selected eye (highest BCVA). Ten consecutive training sessions of 10 min each were performed twice a week in the selected eye with Retimax Vision Trainer (CSO, Florence). BCVA, reading acuity and reading speed, contrast sensitivity, fixation, retinal sensitivity and quality of life questionnaire (VFQ-25) were evaluated at baseline and 7 days following the final session. Results: Significant improvements in terms of BCVA [ p = .011], reading speed [ p = .007], VFQ-25 score [ p = .007], retinal sensitivity [ p = .021] and fixation stability in the central 2° and 4° [ p = .048; p = .037] post-treatment were observed for the 9 patients enrolled, with insignificant improvements observed in reading acuity and contrast sensitivity [ p = .335; p = .291]. Conclusions: Preliminary results support VEP biofeedback rehabilitation improvements for visual function and quality of life in advanced AMD patients with low vision.